Adverse events of colchicine for cardiovascular diseases: a comprehensive meta-analysis of 14 188 patients from 21 randomized controlled trials. Issue 8 (August 2021) - Andreis, Alessandro; Imazio, Massimo; Avondo, Stefano; Casula, Matteo; Paneva, Elena; Piroli, Francesco; De Ferrari, Gaetano M.
Abstract : Aims: Colchicine has an emerging role in the cardiovascular field, although, concerns for side effects, especially gastrointestinal, limit its prescription. We aimed at evaluating reported side effects of colchicine for cardiovascular indications. Methods: We performed a meta-analysis of published randomized controlled trials on colchicine for the treatment of cardiovascular diseases. Random-effects meta-analysis was used to assess the risk of adverse events and drug withdrawal. Publication bias was assessed using the Egger test, and meta-regression was performed to assess sources of heterogeneity. Results: Among 14 188 patients, 7136 patients received colchicine while the other 7052 received placebo. The occurrence of any adverse event with colchicine was reported in 15.3 vs. 13.9% patients [relative risk (RR) 1.26, 95% confidence interval (CI) 0.96–1.64, P = 0.09]. Gastrointestinal events were reported in 16.1 vs. 12.2% (RR 2.16, 95% CI 1.50–3.12, P < 0.001), while diarrhea was reported in 12.5 vs. 8.1% (RR 2.77, 95% CI 1.55–4.94, P < 0.001). The risk of gastrointestinal events increased with daily dose and shorter treatment duration. Myalgias were observed in 21 vs. 18% patients (RR 1.16, 95% CI 1.02–1.32, P = 0.03). Other adverse events such as myotoxicity, hepatic adverse events, hematologic adverse events, cutaneous adverse events, infection or death were not increased by colchicine treatment. Colchicine discontinuation was reported in 4.8 vs. 3.4% patients (RR 1.54, 95% CI 1.20–1.99, P < 0.001). Conclusion: Colchicine is associated with increased risk of gastrointestinal events and myalgias, but not of other adverse events. The risk of gastrointestinal events may be avoided with lower dose (0.5 mg/daily) and is inversely related to treatment duration, possibly due to early drug discontinuation or drug tolerance. Abstract : Supplemental Digital Content is available in the text